Collaborater for a car-like vehicle driven by a user with visual inattention - Chavez, D. (2013)
This paper proposes a control system applied to a car-like vehicle driven by a user. The controller is designed to mitigate the negative effects produced by possible visual distractions of this user. In addition, the paper proposes to evaluate the user?s visual distraction, defining a vector that has two components: one with respect to the path and the other with respect to the obstacles. These elements can be computed on-line and are associated with two time delays that produce a similar effect of instability on the motion of the vehicle. The proposed scheme considers the distraction in the design through such delays. Finally, experiments using a car simulator are carried out.